PENGGUNAAN SEALER SECARA OTOMATIS BERBASIS PLC PADA PERANCANGAN MESIN PACKING KOPI DAN GULA - Sugiharto, Jarot; Sjahrul, Yurika; Hardiansyah, Irwan (Jurnal TEDC; Vol 18 No 1 (2024): JURNAL TEDCDO - 10.70428/tedc.v18i1.805, 2024)
The development of innovation in the home coffee industry has the potential to boost the economy of the community. One commonly encountered problem is with the pressing tool that uses inferior plastic, resulting in inadequate heat production. Therefore, there is a need for development aimed at improving efficiency and increasing coffee packaging production. With the advancement of technology, the use of a sealer proves to be the most effective solution compared to plastic pressing. Several parameters need to be considered, including the heat generated and the sealer's movement during pressing. Hence, this tool utilizes pneumatic technology for the sealer's movement, as it is more effective than using a motor and is directly controlled using PLC